The Determinant of Management Accounting Practices (Case Study in Central Java Banking) - Retno Tri Handayani; Khoirul Fuad; Luluk Muhimatul Ifada (Jurnal Riset Akuntansi dan Keuangan, 2023)
This study examines several contingency factors that influence the application of management accounting practices in a company. The contingency factors in this study include the use of information technology, decentralization and environmental uncertainty. The sample in this study were managers in conventional and sharia banking in the Central Java. This study used PLS test to test the hypothesis. The results of this study have shown that information technology, decentralization and environmental uncertainty affect the application of management accounting practices.